2008
DOI: 10.1088/0034-4885/71/2/026501
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous transport phenomena in Fermi liquids with strong magnetic fluctuations

Abstract: In this paper, we present a recent developments in the theory of transport phenomena based on the Fermi liquid theory. In conventional metals, various transport coefficients are scaled according to the quasiparticles relaxation time, τ , which implies that the relaxation time approximation (RTA) holds well. However, such a simple scaling does not hold in many strongly correlated electron systems. The most famous example would be high-T c superconductors (HTSCs), where almost all the transport coefficients exhi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
233
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(239 citation statements)
references
References 337 publications
(1,013 reference statements)
6
233
0
Order By: Relevance
“…At lower T , the transport in La 1.85 Sr 0.15 Cu 1−y Ni y O 4 has a coherent description in the framework of Fermi-liquid theory, where Kohler's rule is derived under single-relaxation-time approximation with the assumption of small τ -anisotropy over Fermi surface [63,64]. Fulfillment of the rule when ρ 0 is changed by changing temperature indicates nearly T -independent frequency distribution of the phonons involved [65] and is consistent with Fermi-arc length in cuprates being constant [66,67] rather than decreasing with decreasing temperature [68].…”
Section: (B-d)mentioning
confidence: 99%
See 1 more Smart Citation
“…At lower T , the transport in La 1.85 Sr 0.15 Cu 1−y Ni y O 4 has a coherent description in the framework of Fermi-liquid theory, where Kohler's rule is derived under single-relaxation-time approximation with the assumption of small τ -anisotropy over Fermi surface [63,64]. Fulfillment of the rule when ρ 0 is changed by changing temperature indicates nearly T -independent frequency distribution of the phonons involved [65] and is consistent with Fermi-arc length in cuprates being constant [66,67] rather than decreasing with decreasing temperature [68].…”
Section: (B-d)mentioning
confidence: 99%
“…Ni doping can restore antiferromagnetic fluctuations [30,69] that give additional T -dependence in nearly-antiferromagnetic-metals magnetoresistance via correlation length ξ AF (T ), OMR∝ξ 4 AF (T )ρ −2 0 (Ref. [64]). Thus fulfillment of conventional Kohler's rule suggests Tindependent ξ AF within the framework of this theory.…”
Section: (B-d)mentioning
confidence: 99%
“…In this study, we neglect the VC for the current, since its effect is small for ρ and the TEP [35][36][37][38]. The detailed study of the current VC is important for future research.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that magnetoresistance strongly violates the Kohler's rule in the case of CeCoIn5 and CeRhIn5 33 . It has also been observed that the transport properties are modified by the backflow accompanied with anisotropic inelastic scattering 34,35 .…”
Section: Mathematical Formulae Used In the Evaluationmentioning
confidence: 99%